HYBRID TREATMENT OF COMPLEX COMBINED CORONARY AND VALVE DISEASE FOR PATIENTS WITH HIGH LEVEL OF OPERATIONAL RISK - G. V. Aniskevich; M. L. Semenovsky; V. V. Chestukhin; P. A. Vavilov (Вестник трансплантологии и искусственных органов)
The analysis of results of hybrid treatment of complex combined coronary and valve disease at patients with high level of operational risk between January 2005 and December 2010. The hybrid treatment of complex combined coronary and valve disease, provides performance of percutaneous coronary interventions (PCI) in a combinati- on valve surgery. 118 patients, with a median age 64.4 ± 8.9 years, are included in research. 2 approaches of a hy- brid method of treatment – 2-Staged (n = 86) and a method «1-stop» (n = 32) are applied. The оperative mortality has made 4.2%. On the basis of the received results were the conclusion is drawn that at high-risk patients with complex combined coronary and valve disease the hybrid method of treatment allows to lower risk of operation.